Protecting Animal Welfare in Animal-Assisted Intervention: Our Ethical Obligation - Fine, Aubrey H.; Griffin, Taylor Chastain (Seminars in Speech and Language, 2022)
When incorporating therapy animals into clinical practice, there are essential ethical considerations that must be considered to protect the welfare of both the people and the animals who are involved in the intervention. The field of animal-assisted interventions (AAIs) and more specifically animal-assisted therapy (AAT) is just beginning to appreciate the critical role that animal welfare has in enhancing the quality of the entire process of working with a therapy animal. In this article, the authors will present ethical models that are incumbent for practitioners to consider prior to partnering with a therapy animal. Examples of how a speech-language pathologist (SLP) might work with a therapy animal will be integrated throughout the article to demonstrate applied awareness of how good welfare not only protects the animal but also the clients who engage in the intervention. Key aspects to consider at all stages of AAT will be described, including considerations of welfare as they relate to selecting and working with a therapy animal, preparing clients for AAT, and developing specific competencies as an AAT practitioner. Theoretical support for these recommendations will also be outlined, preparing AAT providers to not only incorporate the highest standards in AAT but to also serve as an advocate in championing these standards as the field develops.
Keywords: animal-assisted therapy; animal welfare; therapy animals; ethics in AAI